2020
DOI: 10.1186/s12884-020-03439-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and exercise during pregnancy in Africa: a review of the literature

Abstract: Background Pregnancy is an important phase in a woman’s life, with health status at this stage affecting both the woman and her child’s life. Global evidence suggests that many women engage in low levels of physical activity (PA) and exercise during pregnancy despite its beneficial effects. This is particularly the case in Africa. Methods This article reviews the literature on levels of PA and exercise among pregnant women in Africa, highlighting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 132 publications
(364 reference statements)
1
23
0
Order By: Relevance
“…In Indian, 35.2% [12], in Campinas Brazil, 29% [13], in Colombo Sri Lanka, 13.6% [14], in Pakistan, 20% [15], 27.2% in Serbia [17], and in Gondar town, Northern Ethiopia, 37.9% [16] of the study participants practiced antenatal exercise. The participation of pregnant women in physical activity during pregnancy in Africa is also low [18]. To guide contextual interventions, examining the physical activity during pregnancy is recommended [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indian, 35.2% [12], in Campinas Brazil, 29% [13], in Colombo Sri Lanka, 13.6% [14], in Pakistan, 20% [15], 27.2% in Serbia [17], and in Gondar town, Northern Ethiopia, 37.9% [16] of the study participants practiced antenatal exercise. The participation of pregnant women in physical activity during pregnancy in Africa is also low [18]. To guide contextual interventions, examining the physical activity during pregnancy is recommended [18].…”
Section: Introductionmentioning
confidence: 99%
“…The participation of pregnant women in physical activity during pregnancy in Africa is also low [18]. To guide contextual interventions, examining the physical activity during pregnancy is recommended [18]. However, the status of antenatal exercise practice in Southern Ethiopia has not been assessed yet.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that encompass a multi-ethnic population show lower levels of physical activity among ethnic minority groups. A review of the literature on levels of physical activity and exercise among pregnant women in Africa found that the participation of pregnant women in physical activity was low and declined in step with advancing pregnancy [ 17 ]. The level of physical activity was also found to be low in pregnant women in China [ 18 ] and Taiwan [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research over the past 30 years has shown that regular physical activity during pregnancy has a positive effect on the physical and psychological condition of the pregnant woman, on pregnancy and on fetal development [6][7][8][9][10] . Among mental bene ts are reducing stress, anxiety, and depression as well as wellbeing improvement.…”
Section: Introductionmentioning
confidence: 99%